Revivalism in contemporary Islamic education in Malaysia: a case study of the International Islamic School - Hassan, Nor Jannah (LEGAS, 2012)
The phenomena of Muslim parents feeling the need for alternative education for their children has been distinct in the last two decades. This trend may be associated to parents' increased Islamic awareness in lieu of the islah (reformation), tajdid (renewal) and ihya' (revival) movements in Malaysia and elsewhere. The International Islamic school (established in September 1998) is unique in that it is the first international Islamic school offering a more Islamically integrated education in Malaysia, arguably in the world as well. The chapter presents a detailed case study on the International Islamic School, examining its history, founding philosophy, vision and mission, its academic and non-academic curricula, and its problems and challenges. The chapter is written based on the author's twelve years of experiences and observations as an academic staff, an administrator and a parent of the school, as well as on the findings of a survey conducted in 2010, while the author was heading the school. The case study contributes to a better understanding of the standing of the school, which serves towards improving its services in the scheme of islah (reformation), tajdid (renewal) and ihya' (revival) of the Muslim ummah.